The Urgency of The Principle of Deliberation Towards Regional Institutions in The Perspective of The State of Pancasila Law - Cynthia Hadita; Susi Dwi Harijanti (Veteran Law Review, 2023)
The problem has not been applied optimally and optimally to the principle of deliberation, besides the need for structuring regional institutions so that they can run effectively and efficiently so it needs to be studied from the perspective of the state theory of Pancasila law. The research method used is normative juridical. The results showed that the urgency of regional institutions that refer to the principle of deliberation by remembering that Indonesia is a State of Pancasila Law, one of which needs to practice consultative values, it becomes necessary to construct regional institutions. The RIA method needs to be carried out to consider the costs and benefits in maximizing the implementation of ideal regional autonomy by elaborating on the arrangement of inefficient regional institutions so that they can be implemented optimally.